2022
DOI: 10.1038/s41419-022-04713-z
|View full text |Cite
|
Sign up to set email alerts
|

Complex roles of nicotinamide N-methyltransferase in cancer progression

Abstract: Nicotinamide N-methyltransferase (NNMT) is an intracellular methyltransferase, catalyzing the N-methylation of nicotinamide (NAM) to form 1-methylnicotinamide (1-MNAM), in which S-adenosyl-l-methionine (SAM) is the methyl donor. High expression of NNMT can alter cellular NAM and SAM levels, which in turn, affects nicotinamide adenine dinucleotide (NAD+)-dependent redox reactions and signaling pathways, and remodels cellular epigenetic states. Studies have revealed that NNMT plays critical roles in the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 138 publications
0
38
0
Order By: Relevance
“…It has been shown that NNMT mRNA and protein are both highly expressed in various cancers and NNMT is considered as a potential biomarker and therapeutic target. 37 , 38 A few studies indicated that NNMT was more sensitive than carcinoembryonic antigen (CEA) for diagnosis of lung adenocarcinoma and colorectal cancer (CRC), and combined testing of NNMT and CEA in serum can improve the diagnosis accuracy. 11 , 12 , 39 , 40 The present study explored the underlying mechanisms of NNMT on cell metabolism and inflammatory responses by performing proteomics, secretomics, and metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that NNMT mRNA and protein are both highly expressed in various cancers and NNMT is considered as a potential biomarker and therapeutic target. 37 , 38 A few studies indicated that NNMT was more sensitive than carcinoembryonic antigen (CEA) for diagnosis of lung adenocarcinoma and colorectal cancer (CRC), and combined testing of NNMT and CEA in serum can improve the diagnosis accuracy. 11 , 12 , 39 , 40 The present study explored the underlying mechanisms of NNMT on cell metabolism and inflammatory responses by performing proteomics, secretomics, and metabolomics.…”
Section: Discussionmentioning
confidence: 99%
“…Due to NNMT intervention to a crucial and basically irreversible catabolic reaction of NAM, enzyme activity greatly influences the regulation of intracellular levels of NAM, whose fate is represented by urinary excretion upon N -methylation. NAM is the amide derivative of nicotinic acid (NA) [ 35 ]. In addition to the bioactive compound of vitamin B3, NAM is also a basic precursor of nicotinamide adenine dinucleotide (NAD + ), a pyridine nucleotide coenzyme participating in redox reactions featuring metabolism [ 36 ] and other processes, such as gene expression regulation at transcriptional level and mechanisms of DNA repair in response to structural damage [ 37 ].…”
Section: Nicotinamide N -Methyltransferasementioning
confidence: 99%
“…In addition to the bioactive compound of vitamin B3, NAM is also a basic precursor of nicotinamide adenine dinucleotide (NAD + ), a pyridine nucleotide coenzyme participating in redox reactions featuring metabolism [ 36 ] and other processes, such as gene expression regulation at transcriptional level and mechanisms of DNA repair in response to structural damage [ 37 ]. Since NAM can no longer be used as an NAD + precursor substrate after N -methylation, NNMT activity also plays a fundamental role in regulating the equilibrium between NAD + biosynthesis and breakdown, thus indirectly affecting a wide range of intracellular events [ 35 ].…”
Section: Nicotinamide N -Methyltransferasementioning
confidence: 99%
See 1 more Smart Citation
“…Structures that mimic the N-methyl of 1-MNA (6�8) are also inactive. Single methoxy substitutions at the four-(9, nicotinamide numbering) or two- (10) positions lead to inactivity. Installation of a methylamine at the four-position produces a compound (11) with limited activity.…”
Section: ■ Introductionmentioning
confidence: 99%